Relação entre área de vida e recurso alimentar do lobo-guará (Chrysocyon brachyurus) na borda e em torno do Parque Nacional da Serra da Canastra, Minas Gerais, Brasil - Karem Manuelita Olarte Jimenez (2012)
Little is known about the factors that affect the size of the maned wolf home range and core area. It is the largest canid of South America, near threatened according to the IUCN. Its distribution covers a fragmented and altered habitat, needing to know about the ecology of the maned wolf in these areas to determine the sustainability of them as habitat. The study was done in the area of influence of the National Park of Serra da Canastra (PNSC), found in the phytogeographic region of cerrado with farming. I tested the hypothesis that size of the home range and core area maned wolf is the smaller when it has higher proportion of habitat types with greater resources of small mammals and fruits. Between 2007 and 2012, nine maned wolves were captured by Project Lobos da Canastra. The biomass and numbers of small mammals and fruits were determined from February to July 2012. The sizes of each habitat type with the sizes of the home ranges and core area were correlated. The home range and core area of nine maned wolves with GPS / VHF collars, averaged 54.72 ± 29.04 and 14.99 ± 8.62 km2 (95% Fixed Kernel, 496 and 4635 locations as the minimum and maximum), respectively. Cerrado, coffee plantation, grassland and pasture, in descending order, had the highest biomass per hectare of small mammals (623, 505, 438 e 202 g/ha). Cerrado had the highest biomass of miscellaneous fruit. The pasture had the highest biomass of Solanum lycocarpum. The core areas were negatively correlated with cerrado (rs = -0.943, p = 0.005) and pasture (rs = -0.829, p = 0.042). The results suggest that the size of the core areas responds to the food availability. Around the PNSC, would be more convenient for the maned wolf foraging in cerrado for most biomass available of small mammals and miscellaneous fruit, which is kind of important habitat in the conservation and management of maned wolf in disturbed areas.